Photodamage of the Photosynthetic Apparatus and Its Dependence on the Leaf Developmental Stage in the npq1 Arabidopsis Mutant Deficient in the Xanthophyll Cycle Enzyme Violaxanthin De-epoxidase - Havaux, Michel (American Society of Plant Physiologists, 2000)
The npq1 Arabidopsis mutant is deficient in the violaxanthin de-epoxidase enzyme that converts violaxanthin to zeaxanthin in excess light (xanthophyll cycle). We have compared the behavior of mature leaves (ML) and developing leaves of the mutant and the wild type in various light environments. Thermoluminescence measurements indicated that high photon flux densities (>500 μmol m(−2) s(−1)) promoted oxidative stress in the chloroplasts of npq1 ML, which was associated with a loss of chlorophyll and an inhibition of the photochemical activity. Illuminating leaf discs in the presence of eosin, a generator of singlet oxygen, brought about pronounced lipid peroxidation in npq1 ML but not in wild-type leaves. No such effects were seen in young leaves (YL) of npq1, which were quite tolerant to strong light and eosin-induced singlet oxygen. Non-photochemical energy quenching was strongly inhibited in npq1 YL and ML and was not improved with high-light acclimation. Our results confirm that the xanthophyll cycle protects chloroplasts from photooxidation by a mechanism distinct from non-photochemical energy quenching and they reveal that the absence of xanthophyll cycle can be compensated by other protective mechanisms. npq1 YL were observed to accumulate considerable amounts of vitamin E during photoacclimation, suggesting that this lipophilic antioxidant could be involved in the high phototolerance of those leaves.